“I don’t want to become a scientist”: undergraduate nursing students’ perceived value of course content - Birks, Melanie; Cant, Robyn; Al‑Motlaq, Mohammad; Jones, Janet (Australian journal of advanced nursing, 2011)
Background: In the development and delivery of pre‑registration baccalaureate nursing programs, universities must address both the needs of industry and the registering authorities that regulate health professional practice. Balanced with this, providers of education at this level also wish to deliver an experience to students that they both value and enjoy. Objective: This paper describes the findings of a study examining these factors in the first year of four pre‑registration programs at a rural campus and outreach centre of one Australian university. Design: A descriptive, exploratory survey was employed in this research, which is drawn from a larger study into entry pathway, success and academic experience. Results: Results indicate that students found units such as fundamental nursing subjects and law most enjoyable and valuable. Units with a sociological foundation were considered less enjoyable and valuable. Overall, students recognised the value of the bioscience units while contrarily not expressing enjoyment of this aspect of their studies. Conclusions: These findings have implications for nurse educators in respect of the content and delivery of pre‑registration nursing programs. As first year students, the participants may have been focused on learning fundamental nursing tasks, lacking an understanding of the breadth of knowledge required for their professional role. Future research into aspects of nursing studies found to be most valuable may provide a different perspective if conducted in the period post graduation.